The occupational environment its evaluation, control and management - Anna, Daniel H. (American Industrial Hygiene Association, 2011)
Meet today's critical issues and challenges as an occupational health and safety practitioner, educator, or student with the tools, methodologies and knowledge provided in this reference.--Cover.
AIHI Stock Number: BIHT10-566.
Earlier eds. edited by Salvatore R. DiNardi.
Keywords: Industrial hygiene.; Occupational diseases -- Prevention.; Industrial safety.; elektronické knihy; electronic books